Effect of the Drone and Knapsack Sprayed Herbicides on the Plant Phytotoxicity and Chlorophyll Content in Rabi Groundnut - Chandana Mudigiri; RamPrakash T.; Padmaja B.; Jayasree G; Latha P.C. (Archives of Current Research International, 2024)
Conventional method of herbicide spray application using a knapsack sprayer is cost-effective, easy to operate but leads to inaccurate application of the chemicals, low spray uniformity, unnecessary deposition and non-uniform coverage. In this context, “Unmanned aerial vehicles (UAVs), or aerial drones, are being utilized to decrease the herbicide wastage and increase the efficacy compared to traditional practice. A two year field experiment was conducted with drone at RARS, Research Farm, Palem, Nagarkurnool, Telangana during rabi 2022-23, 2023-24.The model of UAV (drone) used in the bioefficacy and drift studies was battery motive AGRICOPTER AG 365 with UIN UA00132S1EX. Imazethapyr 3.75% + Propaquizafop 2.5% ME (Ready mix) herbicide was sprayed with 25 and 40 L ha-1 of spray volume with flat fan XR11002VP nozzle and flight height was maintained at 2 and 2.5m and knapsack sprayer with 500 L ha-1 of spray volume was taken to study the effect of the drone sprayed herbicides versus conventional spraying practices on plant phytotoxic and chlorophyll content of the leaves and results had shown a non significant effect on chlorophyll content and phytotoxicity.